Effect of a rocking bed on apnoea of prematurity. Issue 6 (June 1982) - Tuck, S J; Monin, P; Duvivier, C; May, T; Vert, P
Abstract : We describe a rocking bed for use in incubators. Its effect was studied in 12 preterm infants with idiopathic apnoea, using each as his own control. All but one had less apnoea when the bed was rocking than when it was still. Apnoea associated with a significant fall in transcutaneous PO2 was less frequent, and fewer interventions were needed to terminate apnoeic attacks.